Analysis of Education Levels of Business Owners and Factors Affecting Business Success in Sago-Based UMKM in Kepulauan Meranti Regency - Wahyuni, Dini; Caska, Caska; Indrawati, Henny (FKIP-Universitas Riau, 2019)
The quality of human resources is an important factor in the midst of intense business competition at the moment. One way to improve human resources is through education. Education is very important because the presence of education will change one's mindset for the better, as well as the importance of education for UMKM business owners. In sago-based UMKM, the level of education of business owners is still relatively low because most business owners only have graduated from elementary school, as well as business success, because 70% of business owners have low incomes and sales have not increased from year to year. Therefore, this research was carried out with the aim of: 1) analyzing the level of education of business owners; and 2) analyze the factors that influence business success. Sampling used propotional random sampling to obtain 80 business owners. The data analysis technique used was descriptive quantitative and multiple linear regression. The results of study found that that the education level of sago-based business owners was still low. The entrepreneurial characteristics, business characteristics, access to capital, marketing capabilities, and government support and business networks have a positive and significant effect on the success of UMKM.